1963
DOI: 10.1063/1.3050984
|View full text |Cite
|
Sign up to set email alerts
|

Color centers in alkali halides

Abstract: The Fourth International Symposium on Color Centers in Alkali Halides, held at the II Physikalisches Institut of the Technische Hochschule, Stuttgart, on August 21–24, 1962, attracted approximately 130 scientists from fifteen countries, with almost half of the attendance coming from the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In fact, this kind of light is commonly used by art historians to make some analyses of paintings, and should not cause any damage to the pigment. These results could agree with the theory of color centers: it is indeed well known that heating or applying an UV radiation will destroy color centers [32].…”
Section: Stain Evolution With Timesupporting
confidence: 81%
“…In fact, this kind of light is commonly used by art historians to make some analyses of paintings, and should not cause any damage to the pigment. These results could agree with the theory of color centers: it is indeed well known that heating or applying an UV radiation will destroy color centers [32].…”
Section: Stain Evolution With Timesupporting
confidence: 81%
“…These new bands are respectively designated as the "A", "B", "C", "D" and "E" bands, as described in Ref. [17]. Parfianovich et al [18] observed induced bands at "B" (peaking at 278 nm), "C" (310 nm), "D" (335 nm) and "E" (400 nm) in X-ray irradiated NaCl:Ag.…”
Section: Resultsmentioning
confidence: 99%
“…The conclusions of these studies indicate that structure of defects for mixed crystals is different in contrast with their pure position. The difference of atomic size between mixed crystals cause to local stresses in lattice and this defeat change crystal properties, its lattice parameters [8][9][10]. In addition, mixed alkali halides found their applications in optical, opto-electronic and electronic devices.…”
Section: Introductionmentioning
confidence: 99%